Workshop Pengembangan Produk dan Konten Marketing sebagai Strategi Pemasaran Digital Produk UMKM Desa Kemetul - Pujiastuti, Anasthasia; Setya Indah Isnawati; Jaya Ramadaey Bangsa; Gagah Dwi Wicaksono; Faturahman Efendi (INDONESIAN JOURNAL OF COMMUNITY EMPOWERMENT (IJCE), 2024)
Kemetul Village is located in Susukan District, Semarang Regency, with the livelihoods of its people as farmers/planters and entrepreneurs. In Kemetul Village, there are many UMKM that utilize the harvest from plants. The understanding of business actors about developing new products from harvests and product marketing strategies that are still lacking, prompted the implementation team to carry out community service in Kemetul Village. Community service activities were carried out from July to September 2024. The methods used included surveys and interviews with village officials and the head of the "Dewi Sri" Women's Farmers Group (KWT) and continued with the implementation of training on product development, packaging design, product licensing, product photos and digital marketing. The conclusion of the community service activities in Kemetul Village is that all training has been carried out well and has had a positive impact on UMKM actors. This activity program produces a diversity of new products, namely tomato fruit juice hard candy, ginger candy, vegetable packs, and peanut oil. The increase in the number of UMKM products that have permits in the form of NIB and SPP-IRT and the increase in the skills of business actors in designing packaging and product photos and digital marketing through social media.   ABSTRAK Desa Kemetul berada di Kecamatan Susukan, Kabupaten Semarang dengan mata pencaharian masyarakatnya sebagai petani/pekebun dan wiraswasta. Di Desa Kemetul terdapat banyak pelaku UMKM dengan memanfaatkan hasil panen dari tanaman. Pemahaman pelaku usaha tentang pengembangan produk baru dari hasil panen dan strategi pemasaran produk yang masih kurang, memicu tim pelaksana untuk melakukan pengabdian kepada masyarakat di Desa Kemetul. Kegiatan pengabdian dilakukan sejak bulan Juli hingga September 2024. Metode yang dilakukan meliputi survey dan wawancara pada perangkat desa dan ketua Kelompok Wanita Tani (KWT) “Dewi Sri” dan dilanjutkan dengan pelaksanaan pelatihan tentang pengembangan produk, pembuatan desain kemasan, perizinan produk, foto produk dan pemasaran digital. Kesimpulan dari kegiatan pengabdian kepada masyarakat di Desa Kemetul yaitu semua pelatihan telah dilaksanakan dengan baik dan memberikan dampak positif bagi pelaku UMKM. Program kegiatan ini menghasilkan diversitas produk baru yaitu hard candy sari buah tomat, permen jahe, sayur pack, dan minyak kacang. Penambahan jumlah produk UMKM yang memiliki perizinan berupa NIB dan SPP-IRT serta bertambahnya keterampilan pelaku usaha dalam mendesain kemasan dan foto produk serta pemasaran digital melalui media sosial.